2012
DOI: 10.2298/aoo1202012d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus DNA in fine needle aspirates of women with breast cancer

Abstract: Background: HPV infection is the most commonly distributed sexually transmitted disease. Human papillomavirus has also been linked to malignant tumors of many human organs. The presence of viral DNA in breast cancer cells is controversial. The aim of the present study was to investigate the presence of HPV-DNA in a group of Greek women with breast carcinoma. Methods: Liquid cytology specimens from 35 malignant breast cases and 35 cases with benign breast lesions were investigated by PCR (clinical arrays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A number of previous studies have clearly addressed the carcinogenic role of HPV as being a necessary cause to induce cancer in humans by transforming the virus-infected cells into a malignant phenotype [15,16]. Some studies have detected the presence of HPV in BC specimens and reported a wide range (4% to 86%) of viral prevalence [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies have clearly addressed the carcinogenic role of HPV as being a necessary cause to induce cancer in humans by transforming the virus-infected cells into a malignant phenotype [15,16]. Some studies have detected the presence of HPV in BC specimens and reported a wide range (4% to 86%) of viral prevalence [9,17].…”
Section: Discussionmentioning
confidence: 99%